(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2024)
The study is interested to gain a general understanding of women’s existence and the limitations or pain they go through in patriarchal cultures, particularly for Firdaus, the main character in the book. 1975 saw the release of the novel Woman at Zero Point in Lebanon. The author wants to convey in terms of equality and justice Gender at that time, we often encounter in everyday life. The research employs qualitative methods. A descriptive analysis was the research methodology used in this project. Steps the researcher took when assessing the data were: Reading, Understand, Analyzing, and Summing up the research results. The research found that are in the novel women are described in 4 categories of gender equality and justice, namely, Gender Injustice, Oppression or cruelty, Violence, and Burden or the role of women. Where there is discrimination and oppression of women both are influenced by a culture that considers the position of men to be higher than the position of women and social status between men and women.